Meta-analysis suggests variable, but pCO2-specific, effects of ocean acidification on crustacean biomaterials - Siegel, Kyle; Kaur, Muskanjot; Grigal, A. Calvin; Metzler, Rebecca; Dickinson, Gary (Dryad, 2022)
Crustaceans comprise an ecologically and morphologically diverse taxonomic
group. They are typically considered resilient to many environmental
perturbations found in marine and coastal environments, due to effective
physiological regulation of ions and hemolymph pH, and a robust
exoskeleton. Ocean acidification can affect the ability of marine
calcifying organisms to build and maintain mineralized tissue and poses a
threat for all marine calcifying taxa. Currently, there is no consensus on
how ocean acidification will alter the ecologically-relevant exoskeletal
properties of crustaceans. Here, we present a systematic review and
meta-analysis on the effects of ocean acidification on the crustacean
exoskeleton, assessing both exoskeletal ion content (calcium and
magnesium) and functional properties (biomechanical resistance and cuticle
thickness). Our results suggest that the effect of ocean acidification on
crustacean exoskeletal properties varies based upon seawater pCO2 and
species identity, with significant levels of heterogeneity for all
analyses. Calcium and magnesium content were significantly lower in
animals held at pCO2 levels of 1500-1999 μatm as compared to those under
ambient pCO2. At lower pCO2 levels, however, statistically significant
relationships between changes in calcium and magnesium content within the
same experiment were observed: a negative relationship between calcium and
magnesium content at pCO2 of 500-999 μatm and a positive relationship at
1000-1499 μatm. Exoskeleton biomechanics, such as resistance to
deformation (microhardness) and shell strength, also significantly
decreased under pCO2 regimes of 500-999 μatm and 1500-1999 μatm,
indicating functional exoskeletal change coincident with decreases in
calcification. Overall, these results suggest that the crustacean
exoskeleton can be susceptible to ocean acidification at the biomechanical
level, potentially predicated on changes in ion content, when exposed to
high influxes of CO2. Future studies will need to accommodate the high
variability of crustacean responses to ocean acidification, as well as
ecologically-relevant ranges of pCO2 conditions, when designing
experiments with conservation-level endpoints. --
Data was collected as either raw values from the main or supplementary
text of a primary research article, or extracted from a visual figure
using WebPlotDigitizer. Values were coded in Excel, saved to a CSV file,
and then processed in R using the 'metafor' package.
CSV files are usable with provided R code. If any issues arise, please
contact Kyle R. Siegel at siegel.kyle9@gmail.com
Keywords: Meta analysis; crustacean; Biomineralization; biomaterial; crab; Calcium carbonate; barnacle; lobster; FOS: Biological sciences